Perceived health and work-environment related problems and associated subjective production loss in an academic population - Malin Lohela-Karlsson; Lotta Nybergh; Irene Jensen (BMC, 2018)
Abstract Background The aim was to investigate the prevalence of health problems and work environment problems and how these are associated with subjective production loss among women and men at an academic workplace. An additional aim was to investigate whether there were differences between women and men according to age group, years at current workplace, academic rank or managerial position. Methods A questionnaire was sent in 2011 to all employees at a Swedish university (n = 5144). Only researchers and teachers were included in the study (n = 3207). Spearman correlations were performed to investigate differences in health and work environment problems. Employees who reported having experienced work environment or health problems in the previous seven days (n = 1475) were included in the analyses in order to investigate differences in subjective production loss. This was done using Student's t-test, One-way Anova and generalized linear models. Results The response rate was 63% (n = 2022). A total of 819 academic staff (40% of the population) reported experiencing either health problems, work environment problems or both during the previous seven days. The prevalence of health problems only or a combination of work environment and health problems was higher among women than men (p-value ˂0.05). This was especially the case for younger women, those in lower academic positions and those who had worked for fewer years at their current workplace. No difference was found for work environment problems. The majority of the employees who reported problems said that these problems affected their ability to perform at work (84-99%). The average production loss varied between 31 and 42% depending on the type of problem. Production loss due to health-related and work-environment related problems was highest among junior researchers and managers. No significant difference between men and women was found in the level of production loss. Conclusion Subjective production loss in academia can be associated with health and work- environment problems. These losses appear similar for women and men even though younger female academics, women in lower academic ranks and those with fewer years of employment in their current workplace report a higher prevalence of health problems and combined work-environment and health problems than men.